Muzyka w terapii logopedycznej dzieci - Budkowska, Monika (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Artykuł poświęcony jest zastosowaniu muzyki w terapii logopedycznej dzieci, poszczególnym technikom oraz ich wpływowi na usprawnianie percepcji i ekspresji głosu oraz mowy. Opisano wpływ muzyki na funkcjonowanie całego organizmu, a także na terapię poszczególnych zaburzeń z pespektywy logopedycznej. Celem publikacji jest przedstawienie różnych form pracy z dźwiękiem i możliwości zastosowania go w terapii dzieci: słuchania, gry na instrumentach, śpiewu, form muzyczno-ruchowych, tańca i innych. Zwrócono uwagę także na rolę muzyki jako formy wspomagania rozwoju w okresie prenatalnym.

The article is about the use of music in speech and language therapy applied to children, individual techniques and their impact on improving the perception and expression of voice and speech. It describes the effect of music on functioning of the whole organism as well as on the therapy of particular disorders from the speech therapy perspective. The aim of the work is to present various forms of work with sound and the possibility of using it in the therapy applied to children: listening to music, playing instruments, singing, music and movement activities, dance and others. Attention was also paid to the role of music as a form of development support in the prenatal period.
Keywords: muzyka; terapia logopedyczna; profilaktyka; music; speech and language therapy; prevention